ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PELAPORAN KEUANGAN PERUSAHAAN MELALUI WEBSITE PERUSAHAAN - Novita Nisa Keumala; Dul Muid (Diponegoro Journal of Accounting, 2013)
Financial reporting is one of the most important information for investors. The development of communications technology so rapidly the company can be utilized to deliver the information needed by investors to more easily and quickly. This study aims to examine the factors that affect the company's financial reporting on the Internet by non-financial companies in the personal website of the company. The variables used in this research are firm size, profitability, industry type, leverage,  outside ownership and systematic risk. This research was conducted by a survey of non-financial companies listed on the Indonesia Stock Exchange in 2011. Technique sampling was used is stratified random sampling. The Hypothesis was examined by logistic regression. The results showed that only the firm size  is positively related on corporate IFR practices and Profitability is negatively related on corporate IFR practices. While other variables, namely, industry type, leverage, outside ownership and systematic risk is not significant.